The development of the agriculture and the village in independent Macedonia - Anakiev, Boris; Jakimovski, Jorde; Gjosheva Kovachevikj, Marija (Faculty of Agricultural Sciences and food, Skopje, 2012)
As part of the economy in Macedonia, the agriculture could have and should have (it was expected) to contribute for the development of the overall economy. There are well relevant indicators for agriculture from which it is concluded that it has given a certain contribution in the overall economy such as: real value of increased GDP, increased export, increased crop per unit capacity etc. However, the key indicators point to unsatisfying realization where the most important are: decreased basic production capacities, an increase of import rather than the increase of export especially for food and others. The comparison among the key indicators for the development of agriculture is made through natural and financial data, by previous comparison of the production capacities, their usage, the change of the production structure and comparison of the crop according to published official data. This paper analyses the socio – economic processes in the Macedonian village and the assumptions and limitations for preservation of the valid agricultural household – analysis of the basic features of the life of the village population, as a significant segment in the lifestyle of the contemporary village. This paper should encourage a creation of model for development and realization of the agricultural policy in Macedonia.
Keywords: agriculture, development, export, village, farm